2005
DOI: 10.1253/circj.69.928
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Uric Acid Concentration and Insulin Resistance and Metabolic Syndrome

Abstract: etabolic syndrome is a cluster of metabolic abnormalities related to an increased risk of cardiovascular disease, 1 and recent research has demonstrated that adipocytokines, especially adiponectin, are associated with metabolic syndrome. 2 In terms of the evaluation and management of hypercholesterolemia (a risk factor of cardiovascular disease and a causative factor of death in more than 40% of heart-related deaths) according to the recommendations of the 2001 Third Report of the National Cholesterol Educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
246
2
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(285 citation statements)
references
References 29 publications
20
246
2
6
Order By: Relevance
“…In a second study, the prevalence of gout in the U.K. adult population was estimated to be 1.4%, with a peak of more than 7% in men aged over 75 years old (5). This trend has also been observed in studies in developing countries in Asia (6,7). Although the studies focused on gout, it is inferred that hyperuricemia incidence has also increased over the same period.…”
Section: Epidemiology Of Gout and Hyperuricemiamentioning
confidence: 81%
“…In a second study, the prevalence of gout in the U.K. adult population was estimated to be 1.4%, with a peak of more than 7% in men aged over 75 years old (5). This trend has also been observed in studies in developing countries in Asia (6,7). Although the studies focused on gout, it is inferred that hyperuricemia incidence has also increased over the same period.…”
Section: Epidemiology Of Gout and Hyperuricemiamentioning
confidence: 81%
“…MetS is characterized by the presence of multiple common cardiovascular risk factors, such as central obesity, atherogenic dyslipidemia (hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C)) levels, hyperglycemia and elevated blood pressure (BP). Elevated SUA levels are prevalent in patients with hypertension 1,2 and MetS, [3][4][5][6][7] and these levels can be a significant predictor of the development of hypertension 3,[8][9][10] and MetS. [11][12][13][14] Although evidence has suggested that elevated SUA levels might have a role in hypertension, 15 a causal relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical and epidemiological studies, SUA has been found to be positively related not only to the risk of hypertension [1][2][3] but also to the risk of atherosclerosis, 4 cardiovascular diseases (CVDs) 5 and metabolic syndrome. 6 To prevent the incidence of hypertension effectively, it has become increasingly important to assign weightage to the influence of individual risk factors.…”
Section: Introductionmentioning
confidence: 99%